Historiography on the imaginary meanings of childhood in the western culture - Rincón Verdugo, Cecilia (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article gives an account of a research commitment developed in the doctoral thesis "Imaginaries about childhood, public policies and pedagogical practices", presented to opt for the title of PhD in Pedagogy-UNAM-2013, which shows how, from the theory of social imaginaries, it is possible to explain the constitution of society and the emergence of social and cultural proposals that question and rethink the social dynamics instituted, as well as the interactions between subjects and culture. With the analysis and interpretation carried out from a qualitative - interpretative historical research approach, the intention is to reveal how imaginaries are forms of legitimation of the social order, a process that occurs between continuities, ruptures, discontinuities; in the key of historical time, each culture has configured that magma of imaginary meanings about childhood present in our western culture, childhood has been shaped in each era, in each society, the living conditions, the treatment, the adult- child and the childhood experience at different times of the development of the West. Methodologically historiography assumed the dynamics of construction of social imaginaries that occurs between the obvious and the opacity, so that, to interpret, unveil and unravel, took -as a documentary source- books, files and articles that allowed to understand how Childhood and children have been investigated and conceptualized at different times in the culture of the West, with which a historiography is made that reveals the permanence or the transformations that have taken place in the form of meaning childhood.